MANAJEMEN SUMBER DAYA MANUSIA DALAM PENDIDIKAN ISLAM - Faisal Fahmi Rambe; Zaini Dahlan, M. Yasir Ridho; Taufik Hidayat (ADISAM PUBLISHER, 2023)
Islamic management and education means the process of utilizing all the resources owned by the Islamic ummah, educational institutions or others. This utilization is carried out through collaboration with other people effectively, efficiently and productively to achieve happiness and prosperity both in this world and in the hereafter. The purpose of writing this article is to provide an overview of Resource Management in Islamic Education. This research uses a descriptive qualitative approach with library research methods. Secondary data sources come from previous literature studies, which include books, journal articles, papers and other studies relevant to the research objectives. The data and information collection method used is a qualitative data collection method using library research; the data is reduced (data reduction), the data is exposed (data display), then conclusions are drawn and verified (conclusion drawing/verifying). The results of this research can be concluded that competent Islamic Education Resources are not obtained instantly but must go through a long process and high commitment. So it can be said that without reliable human resources, Islamic educational institutions will be meaningless and will not have a better effect. If it is not supported by quality human resources, the institution will become an institution that will find it difficult to develop and progress.